Novel advances in strategies and applications of artificial articular cartilage - Chen, Yifei; Zhang, Chenyue; Zhang, Shiyong; Qi, Hexu; Zhang, Donghui; Li, Yifei; Fang, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Artificial articular cartilage (AC) is extensively applied in the repair and regeneration of cartilage which lacks self-regeneration capacity because of its avascular and low-cellularity nature. With advances in tissue engineering, bioengineering techniques for artificial AC construction have been increasing and maturing gradually. In this review, we elaborated on the advances of biological scaffold technologies in artificial AC including freeze-drying, electrospinning, 3D bioprinting and decellularized, and scaffold-free methods such as self-assembly and cell sheet. In the following, several successful applications of artificial AC built by scaffold and scaffold-free techniques are introduced to demonstrate the clinical application value of artificial AC.